2014
DOI: 10.1074/mcp.m114.040865
|View full text |Cite
|
Sign up to set email alerts
|

The O-glycomap of Lubricin, a Novel Mucin Responsible for Joint Lubrication, Identified by Site-specific Glycopeptide Analysis

Abstract: The lubricative, heavily glycosylated mucin-like synovial glycoprotein lubricin has previously been observed to contain glycosylation changes related to rheumatoid and osteoarthritis. Thus, a site-specific investigation of the glycosylation of lubricin was undertaken, in order to further understand the pathological mechanisms involved in these diseases. Lubricin contains an serine/threonine/proline (STP)-rich domain composed of imperfect tandem repeats (EPAPTTPK), the target for O-glycosylation. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 55 publications
2
102
0
Order By: Relevance
“…In vitro experiments have shown that this mutated protein does not undergo the normal process of SPC‐mediated cleavage within the PEX domain (Rhee et al., ), meaning that the PRG4 protein is nonfunctional. Indeed, full‐length protein presents an optimal lubricating function when the intact negatively charges STP‐rich region and positively charged at the N‐ and C‐terminal regions are intact (Ali et al., ; Lee, Muller, Rezwan, & Spencer, ; Swann, Hendren, Radin, Sotman, & Duda, ). In our cohort, we report three siblings with homozygous p.Y1367X (c.4101C>G) mutation predicted to escape the NMD.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that this mutated protein does not undergo the normal process of SPC‐mediated cleavage within the PEX domain (Rhee et al., ), meaning that the PRG4 protein is nonfunctional. Indeed, full‐length protein presents an optimal lubricating function when the intact negatively charges STP‐rich region and positively charged at the N‐ and C‐terminal regions are intact (Ali et al., ; Lee, Muller, Rezwan, & Spencer, ; Swann, Hendren, Radin, Sotman, & Duda, ). In our cohort, we report three siblings with homozygous p.Y1367X (c.4101C>G) mutation predicted to escape the NMD.…”
Section: Discussionmentioning
confidence: 99%
“…The electrostatic repulsion properties of the central mucin domain have been suggested to confer essential boundary lubrication properties, not just for salivary mucins but other similar lubricating glycoproteins such as lubricin found in the synovial fluid of the joint (16). Lubricin has positively charged terminal regions flanking the central negatively charged domain, and these hydrophobic regions are suggested to be important for the adherence of lubricin to the cartilage surface (59). A similar mechanism has been proposed for the boundary lubricating layer of the oral mucosa (60).…”
Section: Discussionmentioning
confidence: 99%
“…2,7,13,14 Lubricin's central, long mucin-like domain is extensively O-glycosylated with Gal(β1-3)GalNAc-O-Ser/Thr, and about two thirds of lubricin's O-glycosylated sites are capped with sialic acid as (α2,3)NeuAc-(β1-3)Gal-GalNAc-O-Ser/ Thr. 2,6,7,[11][12][13][14] Given lubricin's ~200 O-glycosylated sites, 14 there are approximately 133 sialic acid residues per lubricin molecule. Ali et al…”
Section: Discussionmentioning
confidence: 99%
“…9 The central, long mucin domain of lubricin is extensively O-glycosylated with Gal(β1-3)GalNAc-OSer/Thr, and about two thirds of the O-glycosylated sites are capped with sialic acid as (α2,3)NeuAc-(β1-3)GalGalNAc-O-Ser/Thr. 2,6,7,[11][12][13][14] Our aim was to determine whether removal of sialic acid by sialidase could enhance the detection of lubricin with the S6.79 antibody in human tissues by IHC and Western blot analysis. Our data show that the S6.79 lubricin epitope is highly masked by sialic acid in human pericardium, splenic capsule and trabeculae, plasma, serum, eye sleep extract, and liver sinusoids compared with the epitope in normal synovial tissue and fluid.…”
Section: Research-article2016mentioning
confidence: 99%